2020
DOI: 10.3390/cancers12102767
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Biomarkers for Early Detection of Breast Cancer

Abstract: Breast cancer is the most common cancer in women worldwide. Accurate early diagnosis of breast cancer is critical in the management of the disease. Although mammogram screening has been widely used for breast cancer screening, high false-positive and false-negative rates and radiation from mammography have always been a concern. Over the last 20 years, the emergence of “omics” strategies has resulted in significant advances in the search for non-invasive biomarkers for breast cancer diagnosis at an early stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
124
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 189 publications
0
124
0
Order By: Relevance
“…There is no doubt that the early detection of breast cancer is always a good practice, as it results in better outcomes. The breakthrough in the development of noninvasive body fluid-based tests (e.g., blood, urine, tears, sweat and breath) supplemented with the current clinical approaches has a striking potential to increase the precision and accuracy of the earlier detection of breast cancer [ 143 ]. Nevertheless, in patients who fail to be diagnosed early and develop MDR, clinical MDR seems to be independent of the ABC transporter expression, even though various in vitro examples displayed that ABC transporters probably affect the tissue distribution of many chemotherapeutics and directly pump them out to render a chemoresistance.…”
Section: Resultsmentioning
confidence: 99%
“…There is no doubt that the early detection of breast cancer is always a good practice, as it results in better outcomes. The breakthrough in the development of noninvasive body fluid-based tests (e.g., blood, urine, tears, sweat and breath) supplemented with the current clinical approaches has a striking potential to increase the precision and accuracy of the earlier detection of breast cancer [ 143 ]. Nevertheless, in patients who fail to be diagnosed early and develop MDR, clinical MDR seems to be independent of the ABC transporter expression, even though various in vitro examples displayed that ABC transporters probably affect the tissue distribution of many chemotherapeutics and directly pump them out to render a chemoresistance.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, overdiagnosis and radiation are the main concerns for mammography. Breast cancer overdiagnosis by mammogram has been considered as a significant adverse event, as the overdiagnosis probabilities were estimated ranging between 0% and 40-50% depending on subject age and approaches 8 , 26 , 27 . Moreover, this technique is not suited for detecting small-size tumors, especially in women with high breast density 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, autoantibodies against tumorassociated antigens (TAAs) are found to have enormous potential for the exploitation of circulating protein-based biomarkers and have been proposed as hopeful biomarkers for early breast cancer detection [7,8]. TAAs, which have altered protein expression levels, protein misfolding, or aberrant post-translational modifications, can elicit immune responses resulting in the production of autoantibodies [9][10][11].…”
Section: Ivyspringmentioning
confidence: 99%
“…Recently, new approaches for non-invasive biomarkers of BC such as circulating carcinoma antigens, circulating tumor cells, circulating cell-free tumor nucleic acids (DNA or RNA), circulating microRNAs, and circulating extracellular vesicles in a variety of body fluids have been introduced to supplement early detection [ 21 ]. Several studies have indicated an important role of cell-free DNA (cfDNA) as a new promising detection and monitoring method in BC patients [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%